KEPEDULIAN NELAYAN TERHADAP PENDIDIKAN ANAKNYA DI KECAMATAN PADANG SELATAN KOTA PADANG (Studi Kasus Pada Anak Putus Sekolah) - ade Fitria Dori; Dedi Hermon; Zawirman Zawirman (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
The aim of this research is to get information about fishermen’s motivation and attention to their children’s education, the concern of fishermen to their children’s education expenses and education, concern of fishermen to their children’s education fund and facilities in Padang Selatan Subdistrict of Padang City. This research is qualitative descriptive. The informant of the researcher fishermen and his dropout school in Padang Selatan Subdistrict of Padang City. The research found that: 1) The attention and motivation of fishermen towards their child's education in Padang Selatan Subdistrict of Padang City are lack, 2) Concern fishermen to educational facilities to continue their education relatively less, because most of parents have lack responsive to their children needs of educational facilities, 3) The attention of fishermen to the educational fund to continue their childs education are mostly good because the parents have tried to fulfil the fund, but most of the fishermen children whore are dropout seen have not good motivation and attention to their education.